2020
DOI: 10.1073/pnas.1922535117
|View full text |Cite
|
Sign up to set email alerts
|

Cell stemness is maintained upon concurrent expression of RB and the mitochondrial ribosomal protein S18-2

Abstract: Stemness encompasses the capability of a cell for self-renewal and differentiation. The stem cell maintains a balance between proliferation, quiescence, and regeneration via interactions with the microenvironment. Previously, we showed that ectopic expression of the mitochondrial ribosomal protein S18-2 (MRPS18-2) led to immortalization of primary fibroblasts, accompanied by induction of an embryonic stem cell (ESC) phenotype. Moreover, we demonstrated interaction between S18-2 and the retinoblastoma-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
2
14
0
2
Order By: Relevance
“…Stemness, a natural property of MSCs, refers to the capacity of MSCs to maintain self-renewal and an undifferentiated state [ 42 ]. Stemness is important for quiescence, proliferation, and regeneration through the interaction between MSCs and their microenvironment [ 42 43 ].…”
Section: Stemness Characteristics Of Bm-mscsmentioning
confidence: 99%
“…Stemness, a natural property of MSCs, refers to the capacity of MSCs to maintain self-renewal and an undifferentiated state [ 42 ]. Stemness is important for quiescence, proliferation, and regeneration through the interaction between MSCs and their microenvironment [ 42 43 ].…”
Section: Stemness Characteristics Of Bm-mscsmentioning
confidence: 99%
“…Recent studies have shown that ribosomes are involved in multiple biological processes, such as cellular proliferation, differentiation, homeostasis, and development of cancer [ 40 , 42 , 43 ]. Undifferentiated CSCs are known to maintain low levels of global translation and degradation activity, but they need to respond to dynamic alterations in the tumor environment during disease progression by rapidly regulating protein translational programs [ 44 46 ]. Maintaining the ability of CSCs to undergo self-renewal requires high translation efficiency [ 41 , 45 , 47 ], and inhibiting translation in CSCs has the potential to reduce their stem-like properties [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Cheung et al stem cells are proposed to exist in a proliferative or quiescent state [176]. A stem cell encompasses the capability for self-renewal and differentiation through a balance between self-renewing proliferation, differentiate into tissue-specific cell type and quiescence via microenvironment interactions [177]. The microenvironment interactions are governed via ECM mechanics, engineered matrix degradation, cell-adhesive ligands, ECM microstructure, cell-cell interactions, cell-secreted factors, heterologous cell interactions (Figure 12).…”
Section: Maintaining Cell Stemnessmentioning
confidence: 99%